Dance's Mind-Body Problem - Pakes, Anna (Edinburgh: Edinburgh University Press, 2006)
RESUMEN: At the beginning of this article, the hypothetical dancer's answer to Wittgenstein's question about raising his arm suggested mental causation and phenomenal consciousness as important features of dance, which make it more than just movement. If they are indeed fundamental, then they must be central also to any attempt to come to terms with dance philosophically. A position which eliminates either from the picture is unlikely to be able to offer a satisfactory account. Of course, most physicalist would not go so far, but this article has aimed to show how even less extreme physicalist positions encounter difficulties in tackling these aspects of the mind-body problem, and hence in accounting for crucial dimensions of dance activity. This is not to say that a physicalist perspective can never overcome these difficulties, but it does indicate problems that need to be addressed and the appropriateness of a cautious approach to physicalist "solutions" to the mind-body issue within dance.